Preparation method of antibacterial cobalt-chromium alloy false tooth
By mixing cobalt-chromium alloy powder with alumina powder and using selected laser melting molding and nanodiamond film deposition technology, the shortcomings of existing cobalt-chromium alloy denture materials in terms of mechanical properties and antibacterial properties are solved, and efficient antibacterial properties and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411817836.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-07
AI Technical Summary
The existing cobalt-chromium alloy denture materials have shortcomings in terms of mechanical properties and antibacterial properties, and their binding strength with porcelain is poor, which cannot fully meet the needs of denture materials.
The composite powder was prepared by mixing the cobalt-chromium alloy powder with the alumina powder, and the denture matrix was prepared by selective laser melting. Then, transition layer modification and nanodiamond film deposition are carried out to improve antibacterial performance and binding strength.
The good mechanical properties and antibacterial properties of cobalt-chromium alloy dentures are achieved, while the binding strength and duration of the antibacterial layer are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of denture manufacturing, and in particular to a method for preparing an antibacterial cobalt-chromium alloy denture. Background Art
[0002] Cobalt-chromium porcelain alloy was first used in transplantation medicine and used for hip joints. Since the traditional nickel-chromium porcelain alloy used for porcelain teeth has the defects of Ni hazard and poor corrosion resistance of nickel-based alloy, and cobalt-chromium porcelain alloy contains more chromium, has a higher melting point, and there is a certain reaction between the alloy and the embedding material, it has gradually replaced the nickel-chromium porcelain alloy. There are reports in the prior art that the cobalt-chromium alloy material has been improved to make it suitable for dentures, such as the invention patent publication number CN1827814A "a cobalt-chromium alloy containing rare earth La for dental porcelain brackets", and the invention patent publication number CN102002613A "cobalt-chromium porcelain alloy material for dentistry". Although the above patent application has studied and reported on this type of material, it has been improved to a certain extent compared with the prior art. However, it has been proved in practice that the material prepared by it cannot fully achieve the mechanical properties claimed in its specification, and the bonding force with porcelain still needs to be further improved. In addition, the alloy material reported in the above patent does not have antibacterial properties, and it is well known that for denture materials, it is crucial to have good antibacterial properties. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an antibacterial cobalt-chromium alloy denture, which can ensure that the cobalt-chromium alloy has good mechanical properties while giving it good antibacterial properties, while the antibacterial layer has high bonding strength and a longer antibacterial duration.
[0004] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing an antibacterial cobalt-chromium alloy denture, characterized by comprising the following steps: S1, taking cobalt-chromium alloy powder and alumina powder and mixing them in proportion, placing them in an alumina crucible, and preparing composite powder by gas atomization method; S2, taking the composite powder and sieving it to remove impurities and large particles in the powder, drying the sieved powder to remove moisture in the powder, adding the sieved and dried powder from the top of the equipment into the powder cabin of the additive manufacturing system, and realizing cyclic layer-by-layer powder spreading and sintering through selective laser melting to obtain the denture matrix; S3, the denture substrate surface is modified with a transition layer film by an immersion and pulling method in an iron ion-doped titanium dioxide sol, and then placed in a muffle furnace, gradually heated to a target temperature in an oxygen environment, kept warm for a period of time, and then cooled with the furnace, and finally cooled to room temperature in the air to obtain a denture substrate modified with a transition layer; S4, the denture substrate modified with the transition layer is placed in a filtered cathode vacuum arc coating system, and a high-purity graphite target is ionized and deposited on the surface of the transition layer, and finally an antibacterial cobalt-chromium alloy denture is obtained.
[0005] Preferably, the cobalt-chromium alloy powder includes the following chemical components in weight percentage: Cr is 28.4-29.8%, Mo is 5-6%, Mn is 0.3-0.6%, Si is 0.5-0.8%, Fe is 0.2-0.6%, C is 0.8-1.6%, and the balance is Co, and the alumina powder is micron-grade pure alumina.
[0006] Preferably, the mass ratio of the cobalt-chromium alloy powder to micron-grade pure aluminum oxide is 95:5.
[0007] Preferably, the atomization pressure of the gas atomization method in S1 is 5.1-5.8 MPa, and the atomization temperature is 1600-1700°C.
[0008] Preferably, the laser power P of the selected area laser melting forming in S2 is 180-200 W, the scanning line spacing S is 0.04-0.06 mm, and the scanning speed V is 850-900 mm / s.
[0009] Preferably, the specific preparation method of the iron ion-doped titanium dioxide sol in the S3 is: 20.0 ml of butyl titanate, 100.0 ml of anhydrous ethanol and 7.0 ml of triethanolamine are uniformly mixed at room temperature to obtain solution A, 20.0 ml of anhydrous ethanol and 4.0 ml of deionized water are mixed to form a 0.5 mol / L ferric nitrate solution, and then mixed with 0.5 ml of nitric acid to prepare solution B, and solution B is added dropwise to solution A under strong stirring, and after the addition is completed, 2 ml of stabilizer acetylacetone is added dropwise to the solution, stirring is continued for 2 hours, and aging at room temperature is obtained.
[0010] Preferably, the immersion pulling method in S3 is specifically as follows: immersing the denture base into the sol, pulling it at a uniform speed of 2 cm / min, and then placing it in an oven at 100° C. to dry for 8 minutes, and repeatedly pulling the film 5 to 8 times.
[0011] Preferably, the denture base after the immersion and pulling in S3 is placed in a muffle furnace, heated to 1000°C in an oxygen environment, with a heating rate set at 10°C / min, then kept warm for 90 minutes and then cooled to 500°C in the furnace, and finally cooled to room temperature in air.
[0012] Preferably, the working vacuum degree of the filtered cathode vacuum arc coating system in S3 is 1*10 -3Pa, the current of the vacuum arc is 90~92A, and the high-purity graphite target is ionized to form a carbon plasma. After the carbon plasma enters the off-surface double-bend filter device, the transition layer is deposited on the surface in the room temperature vacuum coating chamber. The magnetic field strength of the filter device is 30~35mT, the deposition rate is 3~5nm / min, and the deposition time is set to 10~12min.
[0013] In summary, the present invention has the following beneficial effects: The present invention realizes the production of the denture matrix by mixing cobalt-chromium alloy powder and aluminum oxide powder and adopting selective laser melting molding. Aluminum oxide can effectively improve the corrosion resistance of cobalt-chromium alloy, and the microstructure of cobalt-chromium alloy is fine and the microhardness is good. At the same time, selective laser melting molding makes the internal grains further fine, realizes fine grain strengthening, and thus has good mechanical properties.
[0014] The present invention deposits a transition layer on the denture base first, and then deposits a nano-diamond film on the surface of the transition layer through a filtered cathode vacuum arc coating system. The bonding strength is higher, and the nano-diamond film can significantly reduce the adhesion number of Streptococcus mutans, Candida albicans and Actinomyces viscosus, thereby achieving an antibacterial effect. DETAILED DESCRIPTION
[0015] The specific implementation modes of the present invention are further described below, and these embodiments do not constitute a limitation of the present invention. Example 1
[0016] The specific preparation method of iron ion doped titanium dioxide sol is as follows: 20.0 ml of butyl titanate, 100.0 ml of anhydrous ethanol and 7.0 ml of triethanolamine are uniformly mixed at room temperature to obtain solution A, 20.0 ml of anhydrous ethanol and 4.0 ml of deionized water are mixed to form a 0.5 mol / L ferric nitrate solution, and then mixed with 0.5 ml of nitric acid to prepare solution B, and solution B is added dropwise to solution A under strong stirring, and after the addition is completed, 2 ml of stabilizer acetylacetone is added dropwise to the solution, stirring is continued for 2 hours, and aging at room temperature is performed. Example 2
[0017] A method for preparing an antibacterial cobalt-chromium alloy denture comprises the following steps: S1, taking cobalt-chromium alloy powder and micron-grade pure alumina in a mass ratio of 95:5, mixing the mixture and placing it in an alumina crucible, the cobalt-chromium alloy powder includes the following chemical components in terms of weight percentage: Cr is 28.4-29.8%, Mo is 5-6%, Mn is 0.3-0.6%, Si is 0.5-0.8%, Fe is 0.2-0.6%, C is 0.8-1.6%, and the balance is Co, and a composite powder is prepared by a gas atomization method, the atomization pressure of the gas atomization method is 5.1 MPa, and the atomization temperature is 1600°C.
[0018] S2, take the composite powder and screen it to remove impurities and large particles in the powder, dry the screened powder to remove moisture in the powder, add the screened and dried powder from the top of the equipment into the powder cabin of the additive manufacturing system, and realize cyclic layer-by-layer powder spreading and sintering through selective laser melting. The laser power P is 180W, the scanning line spacing S is 0.04mm, and the scanning speed V is 850mm / s to obtain the denture matrix.
[0019] S3, immerse the denture base into the titanium dioxide sol doped with iron ions, pull it up at a constant speed of 2 cm / min, and then place it in a 100℃ oven to dry for 8 minutes. Repeat this process 6 times to perform transition layer film modification. Then enter the muffle furnace and heat it to 1000℃ in an oxygen environment. The heating rate is set to 10℃ / min, and then it is kept warm for 90 minutes and then cooled to 500℃ in the furnace. Finally, it is cooled to room temperature in the air to obtain the denture base with modified transition layer.
[0020] S4, the denture substrate after transition layer modification is placed in a filtered cathode vacuum arc coating system, and the working vacuum degree is 1*10 -3 Pa, the current of the vacuum arc is 90A, and the high-purity graphite target is ionized to form a carbon plasma. After the carbon plasma enters the off-surface double-bend filter device, the transition layer is deposited on the surface in the room temperature vacuum coating chamber. The magnetic field strength of the filter device is 30mT, the deposition rate is 3nm / min, and the deposition time is set to 10min, and finally an antibacterial cobalt-chromium alloy denture is obtained. Example 3
[0021] A method for preparing an antibacterial cobalt-chromium alloy denture comprises the following steps: S1, taking cobalt-chromium alloy powder and micron-grade pure alumina in a mass ratio of 95:5, mixing the mixture and placing it in an alumina crucible, the cobalt-chromium alloy powder includes the following chemical components in terms of weight percentage: Cr is 28.4-29.8%, Mo is 5-6%, Mn is 0.3-0.6%, Si is 0.5-0.8%, Fe is 0.2-0.6%, C is 0.8-1.6%, and the balance is Co, and a composite powder is prepared by a gas atomization method, the atomization pressure of the gas atomization method is 5.5 MPa, and the atomization temperature is 1650°C.
[0022] S2, take the composite powder and screen it to remove impurities and large particles in the powder, dry the screened powder to remove moisture in the powder, add the screened and dried powder into the powder cabin of the additive manufacturing system from the top of the equipment, and realize cyclic layer-by-layer powder spreading and sintering through selective laser melting. The laser power P is 190W, the scanning line spacing S is 0.05mm, and the scanning speed V is 870mm / s to obtain the denture matrix.
[0023] S3, immerse the denture base into the titanium dioxide sol doped with iron ions, pull it up at a constant speed of 2 cm / min, and then place it in a 100℃ oven to dry for 8 minutes. Repeat this process 7 times to perform transition layer film modification. Then enter the muffle furnace and heat it to 1000℃ in an oxygen environment. The heating rate is set to 10℃ / min, and then it is kept warm for 90 minutes and then cooled to 500℃ in the furnace. Finally, it is cooled to room temperature in the air to obtain the denture base with modified transition layer.
[0024] S4, the denture substrate after transition layer modification is placed in a filtered cathode vacuum arc coating system, and the working vacuum degree is 1*10 -3 Pa, the current of the vacuum arc is 91A, and the high-purity graphite target is ionized to form a carbon plasma. After the carbon plasma enters the off-surface double-bend filter device, the transition layer is deposited on the surface in the room temperature vacuum coating chamber. The magnetic field strength of the filter device is 33mT, the deposition rate is 4nm / min, and the deposition time is set to 11min, and finally an antibacterial cobalt-chromium alloy denture is obtained. Example 4
[0025] A method for preparing an antibacterial cobalt-chromium alloy denture comprises the following steps: S1, taking cobalt-chromium alloy powder and micron-grade pure alumina in a mass ratio of 95:5, mixing the mixture and placing it in an alumina crucible, the cobalt-chromium alloy powder includes the following chemical components in terms of weight percentage: Cr is 28.4-29.8%, Mo is 5-6%, Mn is 0.3-0.6%, Si is 0.5-0.8%, Fe is 0.2-0.6%, C is 0.8-1.6%, and the balance is Co, and a composite powder is prepared by a gas atomization method, the atomization pressure of the gas atomization method is 5.8 MPa, and the atomization temperature is 1700°C.
[0026] S2, take the composite powder and screen it to remove impurities and large particles in the powder, dry the screened powder to remove moisture in the powder, add the screened and dried powder from the top of the equipment into the powder cabin of the additive manufacturing system, and realize cyclic layer-by-layer powder spreading and sintering through selective laser melting. The laser power P is 200W, the scanning line spacing S is 0.06mm, and the scanning speed V is 900mm / s to obtain the denture matrix.
[0027] S3, immerse the denture base into the titanium dioxide sol doped with iron ions, pull it up at a constant speed of 2 cm / min, and then place it in a 100℃ oven to dry for 8 minutes. Repeat this process 8 times to modify the transition layer film, and then put it into a muffle furnace and heat it to 1000℃ in an oxygen environment. The heating rate is set to 10℃ / min, and then it is kept warm for 90 minutes and then cooled to 500℃ in the furnace. Finally, it is cooled to room temperature in the air to obtain the denture base with modified transition layer.
[0028] S4, the denture substrate after transition layer modification is placed in a filtered cathode vacuum arc coating system, and the working vacuum degree is 1*10 -3 Pa, the current of the vacuum arc is 92A, and the high-purity graphite target is ionized to form a carbon plasma. After the carbon plasma enters the off-surface double-bend filter device, the transition layer is deposited on the surface in the room temperature vacuum coating chamber. The magnetic field strength of the filter device is 35mT, the deposition rate is 5nm / min, and the deposition time is set to 12min, and finally an antibacterial cobalt-chromium alloy denture is obtained.
[0029] The present invention realizes the production of the denture matrix by mixing cobalt-chromium alloy powder and aluminum oxide powder and adopting selective laser melting molding. Aluminum oxide can effectively improve the corrosion resistance of cobalt-chromium alloy, and the microstructure of cobalt-chromium alloy is fine and the microhardness is good. At the same time, selective laser melting molding makes the internal grains further fine, realizes fine grain strengthening, and thus has good mechanical properties.
[0030] The present invention deposits a transition layer on the denture base first, and then deposits a nano-diamond film on the surface of the transition layer through a filtered cathode vacuum arc coating system. The bonding strength is higher, and the nano-diamond film can significantly reduce the adhesion number of Streptococcus mutans, Candida albicans and Actinomyces viscosus, thereby achieving an antibacterial effect.
[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions should also be deemed to fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an antibacterial cobalt-chromium alloy denture, characterized in that: The steps include: S1, taking cobalt-chromium alloy powder and alumina powder and mixing them in proportion, placing them in an alumina crucible, and preparing composite powder by gas atomization method; S2, taking the composite powder and sieving it to remove impurities and large particles in the powder, drying the sieved powder to remove moisture in the powder, adding the sieved and dried powder from the top of the equipment into the powder cabin of the additive manufacturing system, and realizing cyclic layer-by-layer powder spreading and sintering through selective laser melting to obtain the denture matrix; S3, the denture substrate surface is modified with a transition layer film by an immersion and pulling method in an iron ion-doped titanium dioxide sol, and then placed in a muffle furnace, gradually heated to a target temperature in an oxygen environment, kept warm for a period of time, and then cooled with the furnace, and finally cooled to room temperature in the air to obtain a denture substrate modified with a transition layer; S4, the denture substrate modified with the transition layer is placed in a filtered cathode vacuum arc coating system, and a high-purity graphite target is ionized and deposited on the surface of the transition layer, and finally an antibacterial cobalt-chromium alloy denture is obtained.
2. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The cobalt-chromium alloy powder includes the following chemical components in weight percentage: Cr is 28.4-29.8%, Mo is 5-6%, Mn is 0.3-0.6%, Si is 0.5-0.8%, Fe is 0.2-0.6%, C is 0.8-1.6%, and the balance is Co. The alumina powder is micron-grade pure alumina.
3. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The mass ratio of the cobalt-chromium alloy powder to micron-grade pure aluminum oxide is 95:
5.
4. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The atomization pressure of the gas atomization method in S1 is 5.1-5.8 MPa, and the atomization temperature is 1600-1700°C.
5. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The laser power P of the selected area laser melting forming in S2 is 180-200 W, the scanning line spacing S is 0.04-0.06 mm, and the scanning speed V is 850-900 mm / s.
6. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The specific preparation method of the iron ion-doped titanium dioxide sol in the S3 is: 20.0 ml of butyl titanate, 100.0 ml of anhydrous ethanol and 7.0 ml of triethanolamine are uniformly mixed at room temperature to obtain solution A, 20.0 ml of anhydrous ethanol and 4.0 ml of deionized water are mixed to form a 0.5 mol / L ferric nitrate solution, and then mixed with 0.5 ml of nitric acid to prepare solution B, and solution B is added dropwise to solution A under strong stirring, and after the addition is completed, 2 ml of stabilizer acetylacetone is added dropwise to the solution, stirring is continued for 2 hours, and aging at room temperature is performed.
7. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The immersion pulling method in S3 is specifically as follows: immersing the denture base into the sol, pulling it at a constant speed of 2 cm / min, and then placing it in an oven at 100° C. to dry for 8 minutes, and repeating the film pulling process 5 to 8 times.
8. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: After the impregnation and pulling in S3 is completed, the denture base is placed in a muffle furnace and heated to 1000°C in an oxygen environment, with a heating rate set at 10°C / min. It is then kept warm for 90 minutes and then cooled to 500°C in the furnace, and finally cooled to room temperature in air.
9. The method for preparing an antibacterial cobalt-chromium alloy denture according to claim 1, characterized in that: The working vacuum degree of the filtered cathode vacuum arc coating system in S3 is 1*10 -3 Pa, the current of the vacuum arc is 90~92A, and the high-purity graphite target is ionized to form a carbon plasma. After the carbon plasma enters the off-surface double-bend filter device, the transition layer is deposited on the surface in the room temperature vacuum coating chamber. The magnetic field strength of the filter device is 30~35mT, the deposition rate is 3~5nm / min, and the deposition time is set to 10~12min.
Citation Information
Patent Citations
Co-Cr porcelain alloy material for dentistry
CN102002613A
Cobalt chrome alloy containing rare earth La for dental ceramic stent
CN1827814A